Tipologi Islam Moderat dan Puritan: Pemikiran Khaled M. Abou el-Fadl - Wahyudi, Chafid (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The study attempts to scrutinize Khaled M. Abou Fadl?s map of thought about typology of Islamic understanding between moderat Islam and puritan Islam within the world Muslim community. The study contains theoretical meaning formula of moderat Islam and the puritan one, the dialectical relationship between them, and conceptual contribution of Khaled M. Abou Fadl on this matter towards islamic studies. The study uses textual interpretation method on Khaled M. Abou el-Fadl?s works. The study concludes that the very basic map of moderat Islamic thought and puritan Islamic thought is found in the Qur?ân.